Hubungan Inisiasi Menyusu Dini dengan Keberhasilan ASI Eksklusif Pada Anak Baduta Di Kota Pekanbaru - Nurhasanah, Nurhasanah; Hermawan, Angga Rizki (Fakultas Kedokteran Universitas Riau, 2025)
The high infant mortality rate (IMR) is one of the problems facing the world. One of the efforts that can be done to suppress the IMR is to give colostrum contained in breast milk as soon as possible in order to increase the immunity and immunity of the neonate. After the first breastfeeding is done, it can be continued with exclusive breastfeeding until the baby is 6 months old. The success of exclusive breastfeeding starts from the optimal implementation of early initiation of breastfeeding (EIBF). The purpose of this study was to determine the relationship between EIBF and the success of exclusive breastfeeding in children under two years old. This type of research is analytic with case control method. Data were taken using a direct interview questionnaire, the research sample amounted to 120 people obtained by purposive sampling technique. Chi-square test was performed to determine the association between EIBF and exclusive breastfeeding. The results showed that most of the breastfeeding mothers aged 26-35 years (63.3%), had EIBF (52.5%), graduated from high school (67.5%), and had moderate knowledge (57.5%), and there was a significant association between EIBF and exclusive breastfeeding (p<0.05) with Odds Ratio (OR) 18.077 (95% CI 7,236 - 45,158).